Development Of Learning Media For Sunday School Children Based On Book Creator To Improve The Mastery Of Learning Materials For Sunday School Children In Pgi Member Churches In The North Tapanuli Region (Journal of Namibian Studies : History Politics Culture, 2024)
Children have an important role in the fabric of society, the growth of civilisation and faith starts from childhood. The status of children in theology is seen in biblical texts including; children are the gift of God (Genesis 33:5), children as the address of preaching the word of God (Deuteronomy 6:4-9), children are the inheritance of the LORD (Psalm 127:3), and heirs of the kingdom of God (Matthew 19:14). These statuses show how important children are before God. Therefore, the church or adults are responsible for teaching children to know God from an early age. In keeping up with the times, the church has opened itself to accept digital learning media such as book creators to replace conventional learning media. This is evidenced by the request of PGI member churches in the North Tapanuli region to be trained in using book creators. Book creator is very helpful for teachers to deliver material on God's word. The steps taken by reveal theological truths in Sunday school teaching materials, produce book creator products, and find out the church's response using the ADDIE method. After the research was carried out, the results showed that the material used by the church in terms of the language of teaching material was still general and tended not to be relevant to the needs of children, the teachers tended not to be competent, the media was still charta but not continuously used. However, after the introduction of book creator-based learning media, the results showed that the teachers responded positively and the product was declared suitable for use.